Use of Fastabiqul Khairat Whale Iskarni Rabi Jonggor Village, Gunung Tuleh Subdistrict, West Pasaman Regency as a Source of Learning Geography Materials of the Biosphere (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Forest is an ecosystem unit in the form of expanses of land containing biological natural resources dominated by trees in their natural environment, which cannot be separated from one another. The study of geography cannot be separated from the reality of human life on the earth's surface as a result of interactions between humans and geographical phenomena on the earth's surface. This study aims to analyze the Utilization of Forest Areas Utilization of Educational Forest Areas of Fastabiqul Khairat Paus Iskarni Rabi Jonggor Village as a source of learning Biosphere Geography material and to find out the factors that inhibit the Utilization of Educational Forest Areas of Fastabiqul Khairat Paus Iskarni Rabi Jonggor Village as a source of learning Geography of biosphere material . Data collection in this study was carried out in a natural setting, that is, primary data sources. Data collection techniques in this study included observation, in-depth interviews, documentation, field notes and literature studies. However, this research will collect more data through observation of the Rabi Jonggor ethnic community, as well as observing the stages passed through participatory observation, in-depth interviews with the Rabi Jonggor ethnic community. The environment (physical, social, or cultural) is a very rich source of learning materials. The environment can act as a source of learning, but also as an object of study (learning resource). The use of the environment as a learning resource often makes students feel happy in learning. Utilization of the environment can develop a number of skills such as observing (with all the senses), taking notes, formulating questions, hypothesizing, classifying, writing, and making pictures or diagrams.